Dechlorane Plus and Related Compounds in the Environment: A Review - Sverko, Ed; Tomy, Gregg T; Reiner, Eric J; Li, Yi-Fan; McCarry, Brian E; Arnot, Jon A; Law, Robin J; Hites, Ronald A (Environmental science & technology, 2011)
Dechlorane Plus (DP) is a high production volume, chlorinated flame retardant. Despite its long production history, it was only recently found in the environment. The first “sightings” of DP were in the North American Great Lakes, but subsequent work has indicated that DP is a global contaminant. For example, DP has recently been detected along a pole-to-pole transect of the Atlantic Ocean. Although it was initially thought that DP was produced only in North America, another DP production plant has recently been identified in China. During the course of characterizing DP in the environment, other “DP-like” compounds were identified. These DP analogs, some created from impurities contained in the starting materials during DP’s synthesis, have also been detected globally. Screening-level modeling data are in general agreement with available environmental measurements, suggesting that DP and it analogs may be persistent, bioaccumulative, and subject to long-range transport and that these chemicals may be candidates for Annex D evaluation under the United Nations Stockholm Convention on Persistent Organic Pollutants. However, more research is required to better quantify the emissions, exposures, and toxicological effects of DP and its analogs in the environment. In particular, there is a need to obtain more monitoring, bioaccumulation, degradation rate, and toxicity information.